ANALISIS PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Perhubungann Komunikasi dan Informatika Kota Semarang ) - Agus Suranta, 08.3502.0743; Wanuri, Wanuri (Students Journal of Economic and Management, 2012)
The research objective was to examine and analyze the effect of motivation on employee kenerja, test and analyze the effect of leadership on employee kenerja, test and analyze the influence of organizational commitment to employee kenerja the Department of Transportation, Communication and Information Semarang City. In this study population were all employees of the Department of Transportation, Communication and Information Semaraang City. The sampling technique used in this study is the sampling technique using non-probability sampling (sampling by not giving equal opportunity to the members of the population to be sampled). Non-probability sampling method used is purposive sampling / judgment sampling. Purposive sampling, the sampling technique to establish certain criteria consistent with the objectives or problems studied. The criteria used for determining the sample is already working at least 3 years, at least high school education and a minimum age of 22 years.Based on the results of model calculations derived summary size adjusted R2 is 0.797 this means that 79.7% of the variation in staff performance can be explained by the variation of the three independent variables of work motivation, leadership and organizational commitment.Based on the results of multiple regression analysis can be seen that motivation has positive effect on employee performance. The effect is statistically significant at 0.020 probability (sig / p <0.005). Leadership positively terhadapkinerja employees. The effect was statistically significant at the probability obtained less than 5% Î± (0.000 <0.05). Organizational commitment positively toward employees performance. The effect was statistically significant at the probability obtained less than 5% Î± (0.000 <0.05). It is identified that all the hypotheses accepted or proven